2018
DOI: 10.4178/epih.e2018019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human and organizational deficiencies on workers’ safety behavior at a mining site in Iran

Abstract: OBJECTIVESThroughout the world, mines are dangerous workplaces with high accident rates. According to the Statistical Center of Iran, the number of occupational accidents in Iranian mines has increased in recent years. This study investigated and analyzed the human and organizational deficiencies that influenced Iranian mining accidents.METHODSIn this study, the data associated with 305 mining accidents were analyzed using a systems analysis approach to identify critical deficiencies in organizational influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The International Council on Mining and Metals (ICMM) reports that its members are committed to safe and sustainable mining by ensuring that health and safety is at the center of all operations and processes (International Council on Mining & Metals, 2019). Despite these commitments and undertakings from industry bodies such as the ICMM, serious accidents continue to occur in the mining industry (Aliabadi, Aghaei, Kalatpour, Soltanian, & SeyedTabib, 2018;Department of Mines and Petroleum, 2016;Dragan, Georges, & Mustafa, 2017). Effective risk management strategies have been identified as the keystone for accident prevention in the mining industry (Department of Natural Resources and Mines, 2017; International Council on Mining & Metals, 2019).…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…The International Council on Mining and Metals (ICMM) reports that its members are committed to safe and sustainable mining by ensuring that health and safety is at the center of all operations and processes (International Council on Mining & Metals, 2019). Despite these commitments and undertakings from industry bodies such as the ICMM, serious accidents continue to occur in the mining industry (Aliabadi, Aghaei, Kalatpour, Soltanian, & SeyedTabib, 2018;Department of Mines and Petroleum, 2016;Dragan, Georges, & Mustafa, 2017). Effective risk management strategies have been identified as the keystone for accident prevention in the mining industry (Department of Natural Resources and Mines, 2017; International Council on Mining & Metals, 2019).…”
Section: Rationalementioning
confidence: 99%
“…Taking each shape to represent studies that featured some form of relationship between organizational factors and the variable, it is evident that about two-thirds of the reviewed studies acknowledged a linkage between organizational factors and accident causation. In particular, six studies (Aliabadi et al, 2018;Lenné et al, 2012;Patterson & Shappell, 2010;Verma & Chaudhari, 2017;Yulianto, Haramaini, & Siregar, 2015;Yunxiao & Yangke, 2014) investigated accident causation using HF tools such as the human factors analysis and classification system (HFACS) developed by Wiegmann and Shappell (2007), including a modified (HFACS-MI) tailored for the mining industry. The major outcomes of the accident analyses using the HFACS tool included the identification of organizational factors as causes or contributory factors of accidents in the mining industry.…”
Section: Relationship Between Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the miners make decisions, the supervision effect of supervisors will affect the miners' expectations of the task's interests; in the decision making, it influences the decision weight function and the psychological value function and then influences the behavior decision, which ultimately affects the safety production level of coal-mine enterprises. And some studies [22,23] comprehensively analyzed human factors and organizational factors involved in mining accidents and determined the relationships among these factors. e results showed that the human factors including skill-based errors, routine violations, and planned inappropriate operation and environmental factors had a higher relative importance in the accidents.…”
Section: Introductionmentioning
confidence: 99%